2023
DOI: 10.1002/fft2.240
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and in vitro assessment of probiotic potential of Lactiplantibacillus plantarum BXM2 from fermented honey passion fruit beverage

Abstract: A potential probiotic strain BXM2 was isolated from naturally fermented honey passion fruit beverage, and identified as Lactiplantibacillus plantarum using 16S rDNA sequence analysis, rpoA gene sequence analysis combined with API bacterial identification method. BXM2 was evaluated for its probiotic and technological properties, such as growth efficiency, gastrointestinal tolerance, antibacterial activity and antibiotic resistance. The results showed that the optimum growth efficiency of BXM2 was achieved under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…plantarum BXM2 isolate (93.99% compared to 55.41%). The coaggregation results align with those of other studies, such as Guan et al [45], in which the coaggregation values of the tested Lpb. plantarum BXM2 isolate with the pathogens E. coli, S. aureus, and S. Typhimurium ranged from 34.05% to 58.34%.…”
Section: Time (H)supporting
confidence: 91%
See 1 more Smart Citation
“…plantarum BXM2 isolate (93.99% compared to 55.41%). The coaggregation results align with those of other studies, such as Guan et al [45], in which the coaggregation values of the tested Lpb. plantarum BXM2 isolate with the pathogens E. coli, S. aureus, and S. Typhimurium ranged from 34.05% to 58.34%.…”
Section: Time (H)supporting
confidence: 91%
“…The coaggregation of probiotics with pathogenic cells contributes to the antimicrobial effect of probiotics against pathogens and has a positive effect on the reduction of gastrointestinal colonization by pathogenic microorganisms [44]. The autoaggregation values obtained in this study are significantly higher than those reported by Guan et al [45] for the tested Lpb. plantarum BXM2 isolate (93.99% compared to 55.41%).…”
Section: Time (H)contrasting
confidence: 64%
“…Among them, the genus Lactiplantibacillus plantarum has extensive track records of ensuring food safety in fermented food production and exhibiting probiotic properties. This strain has been associated with various fermented products, such as fermented chayote, chili pepper, milk, passion fruit beverages, and quinoa. The L. plantarum, renowned for its versatile probiotic properties, plays a crucial role in various sectors, such as the food industry, feed production, and clinical medicine .…”
Section: Introductionmentioning
confidence: 99%
“…In general, processing fruit into wine is an effective strategy to increase its added value. The fermentation process occurs spontaneously due to the metabolic activities of microorganism naturally presented in the raw material or the environment ( Guan et al, 2023 ). The fermentation of fruit wines retains the flavor and nutritional quality of the fruit, providing more unique qualities for it.…”
Section: Introductionmentioning
confidence: 99%